The Factors That Influence Student’s Interest in Continuing Higher Education - Khadijah, Siti; Indrawati, Henny; Suarman, Suarman (Program Pascasarjana, Universitas Riau, 2017)
This study aims to determine the factors that have influence to the interests of the students to continue their education to the higher level. This study population is SMA Negeri 2 Tambang in Kampar Regency. Samples were taken with proportional Stratified Random Sampling as many as 185 people. Analysis of data using mean scores and multiple linear regression.The results of this research show us that motivation, aspirations, wishes, school and family environment are have influence on the interests of students to continue the higher education. The most significant influence variable is the motivation because high motivation will foster a strong interest in the students to pursue the higher education. Meanwhile, the lowest significant influence variable is the school environment because alumni and peers have no influence to students’ interest about higher education. For the students who have the motivation, ambition, willingness expected to improve their achievement and add interest to continue their education to the college, and try to find the complete information about the college that match with their interest and talent. Besides that, the school should give extra motivation to the students to continue their education in the higher level and also provide the complete information about the college that their student want to know about.